Effects of roughing, finishing, and aggressive machining conditions on the milling performance of AISI 1045 steel using TiAlN coated inserts - Rajput, S S (2023)
The objective of the present study is to develop a better understanding of machining performance of TiAlN coated tools during face milling of AISI 1045 medium carbon steel. The influences of three different cutting conditions (roughing, finishing, and aggressive conditions) were investigated on cutting forces, chip temperature, tool wear, surface roughness, and chip characteristics. The highest cutting forces were obtained under roughing condition, while, aggressive mode of machining (high values of cutting speed, feed, and depth of cuts) resulted in the highest chip temperature, crater, and flank wear. Material adhesion and coating delamination were predominant under roughing condition. On the other hand, aggressive condition exhibited diffusion wear causing large depth of crater and severe thermal cracks leading to fracture of the cutting edge. Attrition and abrasion wear were also evident. The results of cutting forces, chip temperature, surface roughness, and chip characteristics were correlated with those of tool wear. Results were found to be beneficial in recommending appropriate criteria for choosing different cutting conditions in face milling of AISI 1045 steel using TiAlN coated insert.